Prospects for the Development of Sago Home Industry ((Metroxylon sp) In Aketobololo Village, Central Oba District, Tidore Island City, North Maluku - Mirnawati Mahangiri; Nur Azizah HS; Abdul Aziz Ramli (International Journal of Education, Information Technology, and Others, 2023)
This study aims to look at the process of selecting raw materials, processing and marketing as well as formulating a strategy for the development of a sago home industry in the villages of Akedotilou and Aketobololo with an emphasis on the aspects of opportunities, weaknesses, threats and challenges that occur in these businesses. This study uses a qualitative method with a descriptive approach. Data analysis used is SWOT analysis. internal factors (strength) that have an influence on the relatively high level of importance: (1) the availability of Raw Materials with an average weight of 0.76, followed by (2) Capital has an average weight of six experts of 0.63 ; (3) the availability of labor with an average weight of 0.56; (4) selling price with an average weight of 0.48; (5) Skills with an average weight of 0.36. Internal factors (weaknesses) that have an influence on the relatively high level of importance: (1) Land Ownership with an average weight of 0.14, followed by (2) Packaging with an average weight of 0.12; (3) Promotion with an average weight of 0.07; (4) There is no Health Standard and BPOM with an average weight of 0.05. 3. external factors (opportunities) that have the highest relative influence or level: (1) strategic industrial position with an average weight of six packs of 0.84, followed by (2) demand for sago with an average weight of 0 .48; (3) socio-cultural conditions with an average weight of 0.39. The results of the evaluation of the EFE matrix, obtained a total score of 3.87 which indicates the business conditions for processing sago flour are moderate or above average. External factors (threats) that have the highest relative importance or influence: (1) business competition with an average weight of six experts of 0.84, followed by (2) natural conditions with an average weight of 0. 68; (3) there has been no government attention with an average weight of 0.36 (4) inadequate road conditions with an average weight of 0.28.